THE RELATIONSHIP BETWEEN COGNITIVE IMPAIRMENT AND NEUROTROPHIC FACTORS IN PATIENTS WITH PARKINSON'S DISEASE DEMENTIA - Rahimbaeva, G.S.; Okhunova, D.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
In addition to describing neurotrophic factors and how they affect brain neurodegeneration and the differentiation and proliferation of nerve tissues, this review article offers the findings of recent research on these topics. Data on the causes and diagnostic indicators of cognitive impairments and their relationship in Parkinson's disease patients are offered.